Impact of Consumer Value on the Selection of a Safe Child Seat - Damian Frej; Paweł Grabski (Communications, 2024)
Unfortunately, nowadays, choosing the right child seat is a real problem, especially for new parents. When choosing a child seat, parents have to consider many factors. These include the method of mounting the seat, the mass of the seat, compatibility with a pram and information about crash tests and approvals. The main purpose of the article is to draw attention to the problem of choosing a safe child seat and the purchasing preferences of parents or legal guardians who decide to buy a child seat. For this purpose, a survey was conducted on a group of 950 people with children. The conducted research has shown that the main parameter influencing the choice of a child seat is the price for men and the social opinion and mass of the child seat for women. In addition, research has shown that most people decide to buy a child seat based on the installation system using a standard ISOFIX base.